DELAY OF ERUPTION IN PEDIATRIC PATIENTS WITH NEPHROCALCINOSIS - Pinto, José Miguel (2016)
Objectives. The objective of this research was evaluate the delay of rash in patients Pediatric with diagnosis of nephrocalcinosis, that come to consultation to the area of Nephrology Pediatric of the city hospital Enrique Tejera in the period january-june 2015, since the eruption dental is a process physiological complex that continues a chronology, sequence and time of eruption, that can verse influenced by different factors as the sex , age, race and condition systemic. Materials and methods. It was a descriptive-comparative research where 20 panoramic radiographs, of which 10 were from patients with nephrocalcinosis and 10 from systemically healthy patients were evaluated. Nolla and Demirjian analysis were applied in order to compare chronological age with dental age and thereby to assess the presence of eruption delay. Results. 50% of patients with nephrocalcinosis and 20%of patients systemically healthy with eruption delay were shown, identified through Nolla analysis .